Unlocking academic potential: framework for effective research utilization and commercialization in higher education institutions - John Joshua Federis Montañez; Anna Liza Mendrique Mateo (Institute of Advanced Engineering and Science, 2026)
Traditional academic research pathways in higher education institutions (HEIs) often emphasize publication and extension activities, while the utilization and commercialization of research outputs remain underdeveloped. This study aims to assess the institutional readiness, strategies, challenges, and success metrics related to research utilization and technology commercialization in state universities and colleges (SUCs), and to develop a framework to strengthen entrepreneurial and innovation-driven practices in HEIs. A mixed-methods approach was employed, combining case study analysis with a survey of nine SUCs in the Bicol Region, Philippines. The survey instrument was developed through key informant interviews (KIIs) and focus group discussions (FGDs) with experts in technology transfer and intellectual property (IP) management, and demonstrated excellent reliability (Cronbach’s α=0.92). Results indicate that all participating SUCs have dedicated offices for IP management and technology transfer, reflecting a high level of institutional readiness. However, major challenges persist, including limited funding, weak industry linkages, gaps in IP policy implementation, and the absence of sustainable revolving funds. Success in commercialization is primarily measured through patent filings, licensing agreements, and revenue generation, with limited use of qualitative impact indicators. The study concludes that while SUCs exhibit strong structural readiness, strengthening policy coherence, funding mechanisms, industry collaboration, and commercialization culture is essential. The proposed framework provides a practical guide for enhancing research utilization and commercialization in HEIs.